2009
DOI: 10.3109/00952990903322865
|View full text |Cite
|
Sign up to set email alerts
|

Dropout from Interim Methadone and Subsequent Comprehensive Methadone Maintenance

Abstract: Background-Methadone maintenance in the U.S. is delivered primarily through specialized clinics that provide psychosocial services together with medication. Interim methadone (IM) is an evidence-based approach to increase access by providing methadone without counseling for individuals waiting for admission to comprehensive treatment. Little is known about the role of patient characteristics in predicting outcomes in the IM service pathway (IM with comprehensive methadone treatment following IM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Others may prefer short-term treatment because they are highly motivated to cease their drug use and desire to be abstinent from all opioids, including medications. Some studies support motivation as a prospective correlate of retention (Booth, Corsi, & Mikulich-Gillbertson, 2004; Simpson & Joe, 1993), while others have not found this relationship (Gryczynski et al, 2012; Gryczynski, Schwartz, O’Grady, & Jaffe, 2009). Unfortunately, the parent study did not include instruments measuring patient motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Others may prefer short-term treatment because they are highly motivated to cease their drug use and desire to be abstinent from all opioids, including medications. Some studies support motivation as a prospective correlate of retention (Booth, Corsi, & Mikulich-Gillbertson, 2004; Simpson & Joe, 1993), while others have not found this relationship (Gryczynski et al, 2012; Gryczynski, Schwartz, O’Grady, & Jaffe, 2009). Unfortunately, the parent study did not include instruments measuring patient motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Gender has not consistently predicted entry or retention 1,2931 , although there is some evidence to suggest that men are more likely to be retained 28,32 . While some studies have found treatment readiness for cessation of drug use to be an important influence on retention 11 in different treatment modalities (e.g., long term residential, outpatient, methadone) 20,25,33,34 , others have not found this relationship 35,36 , particularly among samples of African-American patients 35,37 . Similarly, poor mental health may worsen retention in buprenorphine treatment in some studies 38 , while other studies have suggested a link between depressive symptomatology and retention 47,48 .…”
Section: Introductionmentioning
confidence: 98%
“…Patient treatment motivation at intake in patients with drug dependence was also associated with the formation of better therapeutic relationships, more favorable perceptions of counselor competence, support from peers, and increases in session attendance Broome, Simpson, and Joe 1999;Meier et al 2005). However, other studies found no association between pretreatment motivation and treatment engagement, subjective reasons for drop-out, or with treatment outcomes in patients in methadone maintenance programs (Gryczynski et al 2009a(Gryczynski et al , 2009b.…”
mentioning
confidence: 98%